PARAMETER PERTUMBUHAN RAJUNGAN (PORTUNUS PELAGICUS) DI PERAIRAN ASAHAN SUMATERA UTARA - Friyuanita Lubis; Mira Mauliza Rahmi (Journal of Aceh Aquatic Sciences, 2022)
Asahan waters, North Sumatra, is an area bordering near Malacca Strait used as a fishing ground for fish and blue swimming crabs (Portunus pelagicus). The consumed crabs as well as encourage the increasing demands globally. Stock management of biota aquatichad to sustainon thesustainability. This study should include informations on carapace width distribution, growth rate, mortality rate, exploitation rate and recruitment pattern. The data was obtained based on observations, enumerations and interviews at landing sites. Results showed that the crabs caught in January 2021 were 680 males and 324 females. Asymptotic carapace width (CW∞) of 125.7 mm for males and 118.0 mm for females, growth rate (K) 3.0/year for males and 0.9/year of females, total mortality rate(Z) 5.70/year for males and 1.42/year for females, natural mortality rate (M) 2.50/year for males and 1.16/year for females, mortality rate due to fishing (F) 3.20/year for males and 0.26/year for females. The exploitation rate of males (E= 0.56/year) reached overexploitation and the female (E= 0.19/year) has not exceed the optimal level. These results provide an approach on stock management of crabs based on the time of capture during spawning and recruitment in order to maintain the population sustainability.